Validity Analysis of Ethno-Inquiry Integrated Digital Teaching Materials to Facilitate Creative Thinking and Students' Science Process Skills - Nabilla Mutiara, Adela (Physics Learning and Education, 2025)
Creative thinking skills and science processes are the main demands in 21st century learning, especially in physics subjects that demand conceptual understanding and exploratory abilities. However, the reality in the field shows that physics learning is still conventional and minimal utilization of contextual and digital media. To answer this problem, ethno-inquiry integrated digital teaching materials were developed as an innovative solution that combines technology, local culture, and scientific approaches. The purpose of this research is to develop and analyze the validity of digital teaching materials to facilitate students' creative thinking skills and science process on heat material. This research uses the Research and Development (R&D) method with the Hannafin & Peck model through the stages of needs analysis, design, development, and implementation. Validation was conducted by three experts using instruments covering five main aspects: material substance, visual communication, learning design, software utilization, and ethno-inquiry integration. The validation results showed that all aspects obtained an average score of 0.92 which was classified as "valid". These teaching materials were designed using Canva and presented through the heyzine flipbook platform, which provides an interesting and contextual digital learning experience. Thus, this teaching material is proven to be valid and has the potential to be an alternative physics learning that is adaptive to the Merdeka Curriculum and 21st century skills-based learning needs.